Colloidally synthesized Cu3VS4 nanocrystals as a long cycling anode material for sodium-ion batteries - Kelly Murphy; Deaglán Bowman; David McNulty; Tadhg Kennedy; Hugh Geaney (Electrochemistry Communications, 2024)
We report on the colloidal synthesis of Cu3VS4 nanocrystals as an earth abundant anode material for sodium-ion battery applications. The nanocrystals were structurally characterized prior to testing in half-cells, where they displayed excellent cycling stability up to 1000 cycles, demonstrating the potential of colloidally synthesised materials for sustainable battery applications.